A ficção e o real: a importância da educação no século XIX - Corrêa, Giseli Rodrigues (2009)
It is an analysis of the education process in the formation of the youth in the XIX century, taking for base the works fiction of a Brazilian and Portuguese writers, besides the knowledge in place and texts about the ancient College Caraça, model in that epoch, situated in Minas Gerais. Leaving from our research object, the novel O Ateneu, from Raul Pompéia, through the memories of Sérgio, the protagonist, revealed the function of one of the best colleges in Rio de Janeiro of the XIX century: austere discipline and basic mistakes not apparent at fathers eyes who were sending their children to study in the boarding school. So, we like to answer the next question: might we understand that the character Sérgio reveals Pompéia, as soon as he reproduces the characteristics of his creator? The identity of the character, trought the memory, can be seen as a projection of the author? The narrative elaborated of Sérgio perspective, already ripened through his impressions and sharp perception, analyses facts and situations that structured the social environment of the boarding school. The episodes served how revealed successive of the corruption and the moral misery that they were ruling in the traditional College Abílio, that it was frequented by Pompéia. In this sense, it was possible to draw a parallel between this work and Os Maias and A Reliquia of Eça de Queiroz, since they show the importance of the education in the life s formation of Carlos Eduardo and Teodorico, that, unfortunately, little used it, because the first one, although it had an exemplary education financed by his grandfather, surrendered to the enchantments of his sister Maria Eduarda, that after surviving the incest and killed Afonso of displeasure; already the second used an education hypocritical and religious to inherit the fortune of his aunt, Sr.ͣ Patrocínio, and was unmasked through a relic. All the novels wanted to show the importance of the education in the formation of people. Therefore, it was realized a research in a real establishment: the College Caraça, which worked like boarding school and seminar during the XIX century, to make a possible demonstration of model education; concern it was of Ramalho Ortigão with his children and his grandchildren